2022
DOI: 10.23917/reaksi.v7i1.17313
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Pricing Aggressiveness, Thin Capitalization, Political Connection, Tax Avoidance: Does Corporate Governance Have A Role in Indonesia?

Abstract: This study investigates the association of transfer pricing aggressiveness, thin capitalization, and political connection with tax avoidance and the corporate governance's role in moderating these associations. The secondary data of this study are data and information obtained from financial reports and annual reports sourced from www.idx.co.id and www.idnfinancials.com. The analysis is conducted on 61 non-financial multinational companies listed on Indonesia Stock Exchange over the 2016-2019 period, chosen by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 63 publications
2
17
0
16
Order By: Relevance
“…Second, this research fills a gap in the association between political connection and tax aggressiveness as the previous researches found competing results (Wahab et al. , 2017; Kim and Lee, 2021; Fasita et al. , 2022).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, this research fills a gap in the association between political connection and tax aggressiveness as the previous researches found competing results (Wahab et al. , 2017; Kim and Lee, 2021; Fasita et al. , 2022).…”
Section: Introductionmentioning
confidence: 85%
“…Although previous studies have found that political connection is positively associated with tax aggressiveness (Wahab et al, 2017;Wang and You, 2022), researchers in Indonesia have reported mixed findings (Iswari et al, 2019;Fasita et al, 2022). The mixed results are due to firms' business ethics.…”
Section: Political Connection Tax Aggressiveness and Business Ethicsmentioning
confidence: 93%
See 1 more Smart Citation
“…Table II identifies articles in various journals. Based on the analysis, it appears that in the second stage of adoption the researcher is more interested in studying the impact of tax avoidance on companies which is associated with various variables that are often used in tax avoidance research such as Fasita et al (2022), Firmansyah et al (2022), Abdelfattah and Aboud (2020), Kiesewetter andManthey (2017), andBayar et al (2018) which links tax avoidance with corporate governance other studies (Firmansyah et al, 2022), (Rustiarini & Sudiartana, 2021), which link avoidance taxes with a political connection (Stawati, 2020), (Irawati et al, 2020), (Prastiyanti & Mahardhika, 2022) which link tax avoidance with profitability. Other research conducted by Rossa (2022), Sinaga and Malau (2021), and Rifai and Atiningsih (2019), and this study linked tax avoidance with capital intensity; this is different from research conducted by Rifai and Atiningsih (2019), Bose (2021), andLee (2019), which links the avoidance of taxes on companies with earnings management.…”
Section: B Article Identificationmentioning
confidence: 99%
“…Furthermore, when it needs to implementing tax avoidance, this is already related to the separation Shareholders/management as their provider opportunities toward the managers as chance of advantage for tax avoidance behavior and being engaged in self-serving behavior that possibly harming the company's value. Another study from Frank (2020), has been stated if the research conducted did not discuss about how every benefit and other cost of implementing an imputation system for tax evasion, as well as (Fasita et al, 2022) research related with tax limitation and still couldn't be generalized for different periods as much as multinational companies' scope also were not listed on the Indonesian Stock Exchange, or many multinational companies' stock in other countries.…”
Section: Introductionmentioning
confidence: 99%